Natural thinker - Lipsher, Steve, author; Denver Post, publisher (Colorado State University. Libraries, 1997)
Thirty years after he laid the foundation for environmental ethics, Holmes Rolston continues to wrestle with one of the West's most contentious issues, bridging the human and the natural world. So revolutionary has Rolston's work been that this spring he won an invitation to Scotland to present the prestigious Gifford Lectures, an 110-year old lecture series that has featured some of the world's most creative and influential philosophers and scholars.
Photos by Jill Mott.
Keywords: biography; Gifford Lectures; science; Rolston, Holmes, 1932-2025; environmental ethics; religion